El precedente judicial en el derecho comparado - Victoria Parra, María (2011)
The author gives an account of how the incorporation of judicial precedent has meant a considerable modification in the traditional system of sources of law in this country on the one hand, and on the other shows the transformation that this implies on the subject of legal administration, as judges move from being mere executors of legal texts to constructors of alternatives in areas without legislation. Finally, a review is made of the criteria to which the Constitutional Court has taken recourse, as the ultimate interpreter of the Constitution, in order to make the theory of judicial precedent compatible with the requirements of art. 230 of Fundamental Law.